Case report: A rare manifestation of vasospasm induced myocardial infarction with ST-segment elevation in a young male patient - Diečkus, Laurynas; Rodevič, Greta; Baranauskas, Arvydas; Davidavičius, Giedrius; Budrys, Povilas (Frontiers in Cardiovascular Medicine, 2023)
Background Minority of acute myocardial infarctions (MI) are caused by a non-atherosclerotic occlusion of the coronary artery. We present a case report, where MI with ST-segment elevation was provoked by a vasospasm, which is a rare aetiological finding. Case presentation 27-year-old male patient presented to the emergency department because of a sudden onset chest pain radiating to the left arm. The patient underwent percutaneous coronary intervention (PCI) to the right coronary artery (RCA) 3 months ago due to inferior wall MI, however, chest pain episodes kept on recurring at night throughout the whole period after the intervention. During current admission, initial electrocardiogram (ECG) demonstrated ST-segment elevation in leads II, III and aVF. Coronary angiogram revealed diffuse severe narrowing of the right coronary artery, which was relieved with intracoronary administration of nitrates and verapamil. After coronary angiogram patient was given oral long-acting nitrates and verapamil, however, during the following days nocturnal chest pain episodes reoccurred. It was decided to swap verapamil to diltiazem, which led to complete cessation of angina episodes. The patient was discharged in stable condition and symptom free. It was suspected that the first MI was of vasospastic origin, which likely led to unnecessary stenting. Conclusions This clinical case has demonstrated the challenges clinician could face in order to correctly diagnose vasospasm-induced MI because of its rare occurrence and highly variable presentation. We strongly suggest using intracoronary nitroglycerine during coronary angiography as a standard practice to avoid a potential diagnostic error and unnecessary stenting. Although, in some cases the reason behind coronary artery spasm (CAS) remains unclear, medical treatment can be very effective for CAS prevention.